Sociodemographic factors and career growth as determinants of staff retention among nurses in a military hospital in Saudi Arabia - Amal Bany Ateah; Ahmad Aboshaiqah; Ahmad M. Rayani (Medicine, 2026)
Nurses are the backbone of healthcare systems, and their retention remains a critical global challenge, as high attrition leads to a loss of expertise, continuity of care, and patient trust. The main objective of this study is to examine whether sociodemographic factors and career growth act as determinants of staff retention among nurses working in a military hospital in Saudi Arabia. A cross-sectional analytic study was conducted among nurses employed at an Armed Forces Hospital in Saudi Arabia over a 3-month period between June and August 2025. Data were collected using an online self-administered questionnaire distributed via social media platforms. The questionnaire included sections on sociodemographic characteristics, career growth, and turnover intention. Statistical Package for Social Science (SPSS) version 27 was used to analyze the data. A total of 350 nurses completed the questionnaire, yielding a response rate of 92.1%. Most nurses reported positive perceptions of career growth, with 78.3% indicating improved emotional control and 48% strongly agreeing that their professional competence had improved. Over half of the participants (51.7%) strongly agreed that their professional prestige had increased due to work achievements, and many perceived timely promotions according to organizational ladders. Turnover intention was low, as 66.9% strongly disagreed with having considered leaving their job, and 75.4% strongly disagreed with frequently thinking about seeking alternative employment. The mean career growth score was 66.71 ± 19.78, while the mean turnover intention score was 10.83 ± 3.92. A strong negative correlation was found between career growth and turnover intention ( r = −0.718, P < .001). Nurses in this military hospital demonstrated positive perceptions of career growth and low turnover intention, reflecting high job satisfaction and organizational commitment. Enhancing career development opportunities may play a crucial role in sustaining nurse retention within military healthcare settings.